THE CHANGING OF CHARACTERIZATION OF THE MAIN CHARACTER IN DAVID NICHOLLS’ ONE DAY - Ines Yudika Sihombing; Johan Sinulingga (LINGUISTICA, 2014)
ABSTRACT This study deals with The Changing of Characterization of The Main Characters in David Nicholls’ One Day. The objectives of this study are to find out the changing of characterization and the reasons that cause the changing in the novel. This study is limited to analyze Dexter Mayhew as the main character. This study applied descriptive qualitative method. The data were taken from David Nicholls’ novel One Day. The findings indicate that Dexter has round and negative side as his nature; Arrogant, Ambitious, Hedonistic and Selfish. The character finally ended to the positive characterization;  being responsible and mature. The reason causing the changing of characterization of the main character is that facing a major outside challenge, developing a close relationship with someone very diffrent from himself such as Sylvie, Jasmine and Emma, and facing his own inner demons and prejudices. Keywords: Prose, Character, Round, Changing Characterization